(3GdJLQHI GdLRGFQjI aj JfXje GdJLGQI GdNGQLjI (B:s (3ef GMJcGQ GdOhdI Gdi GMJcGQ GdNhGU (B/s - (3YLI, GdLjdGdjs ((3GdLRGFQ(B: s (3OGQ GdNdOhfjI(B, s, 2007)
(3SdWI GdOhdI GdGTJQGcjI h GNJjGQ GdGMJcGQ h SdWI GYGOI GdgjcdI h GNJjGQ GdGfaJGM , GSJbdGdjI GdJLGQI GdNGQLjI h GdJYOjd Gdgjcdj dgGs
(3HjHdjhZQGajG U(B.291(3; agQS GdLOGhd U(B.309s
Keywords: (3GdEMJcGQs; (3GdJLGQI GdNGQLjIs; (3GdJLGQI GdNGQLjI(B- (3GdLRGFQs